2018
DOI: 10.1039/c8sm01448e
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and microstructure of concentrated microcrystalline cellulose (MCC)/1-allyl-3-methylimidazolium chloride (AmimCl)/water mixtures

Abstract: Water added to a solution of microcrystalline cellulose (MCC) in 1-allyl-3-methylimidazolium chloride (AmimCl) reduces the solvent quality and causes significant changes in the flow properties and microstructure due to restructuring and aggregation of cellulose molecules. We report an experimental investigation by means of polarization optical microscopy (POM) and rheology of the distinct phases formed in 5-20 wt% MCC/AmimCl solutions due to the addition of water. With increase in the cellulose concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…In this study, the structure and crystallinity of regenerated cellulose fibers are regarded as cellulose II crystalline. The change in crystallography indicates the cleavage of initial intermolecular hydrogen bonds in cellulose in the AMIMCl solutions, ultimately leading to the dissolution of cellulose as a viscose [ 40 ]. As mentioned above, the dissolution and regeneration of cellulose in this work can be described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the structure and crystallinity of regenerated cellulose fibers are regarded as cellulose II crystalline. The change in crystallography indicates the cleavage of initial intermolecular hydrogen bonds in cellulose in the AMIMCl solutions, ultimately leading to the dissolution of cellulose as a viscose [ 40 ]. As mentioned above, the dissolution and regeneration of cellulose in this work can be described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of temperature, the intersection point moved toward the high-frequency area, where modulus transposition occurs, and the sample experienced structure reconstruction and an elasticity larger than the viscosity, which are typical characteristics of an entangled polymer solution. Under the same oscillation frequency, when the temperature increased, G' and G" decreased, which indicated that the viscoelasticity decreased [54][55][56].…”
Section: Thermal Analysismentioning
confidence: 93%
“…This has been experimentally verified for solutions of several polymers, including cellulose. ,, Moreover, the generation of an anisotropic phase by this route, in principle, is not solvent specific. The poor solvent quality can be achieved by manipulating temperature or using a suitable antisolvent. , Recently, we have shown the formation of anisotropic gels in cellulose/IL mixtures with the addition of water . At low concentration of cellulose (5 and 7 wt %) in the ILs, LC domains are observed to form with an increase in the concentration of water (antisolvent).…”
Section: Introductionmentioning
confidence: 99%
“…At low concentration of cellulose (5 and 7 wt %) in the ILs, LC domains are observed to form with an increase in the concentration of water (antisolvent). Whereas, superior mechanical properties are observed only at higher concentrations of cellulose (at 15 and 20 wt %), with the formation of a scale-invariant, self-similar gel of space spanning network of spherulitelike morphology . The formation of a spherulitic network at high cellulose concentration has been hypothesized to be because of the increased probability of local aggregation of cellulose chains causing more compact spherulitelike structures.…”
Section: Introductionmentioning
confidence: 99%